Relationship between Sports Aggression and Sports Mindfulness with Sports Self-efficacy in Male Athletes; the Mediating Role of Family Cohesion - Aryan Hatami Gharibvand; Behnam Makvandi; Alireza Heidari (Men's Health Journal, 2022)
Introduction: Self-efficacy is a construct that can greatly influence sports development. Individuals with a high self-efficacy level are more likely to set tougher goals and work harder to achieve them. We aimed to investigate the relationship between sports aggression and sports mindfulness with sports self-efficacy in male athletes through the mediating role of family cohesion. Material and Methods: The statistical population of this descriptive-correlational study covered all male athletes who are members of the youth and adult male football teams in Masjed Soleyman (Iran) in 2021. The 258 athletes were selected using convenience sampling. The research tools included the Sports Self-Efficacy Questionnaire, the Buss-Perry Aggression Questionnaire, the Mindfulness Inventory for Sport, and the Family Cohesion Questionnaire. The proposed model was evaluated using path analysis and indirect correlations were tested with bootstrapping. Results: The results suggested that all direct paths to sport self-efficacy were significant except sports mindfulness (P<0.01), and indirect paths to sports self-efficacy became significant through family cohesion (P<0.01). Conclusion: The proposed model had a good fit, and was a major step toward recognizing the factors affecting sports self-efficacy in male athletes, and can help in designing programs to reduce their experienced tension and improve their sports self-efficacy.